Inhibition of fatty acid synthase with FT‐4101 safely reduces hepatic de novo lipogenesis and steatosis in obese subjects with non‐alcoholic fatty liver disease: Results from two early‐phase randomized trials. Issue 3 (21st December 2020) - Beysen, Carine; Schroeder, Patricia; Wu, Eric; Brevard, Julie; Ribadeneira, Maria; Lu, Wei; Dole, Kiran; O'Reilly, Terry; Morrow, Linda; Hompesch, Marcus; Hellerstein, Marc K.; Li, Kelvin; et al.
Abstract: Aims: To assess the therapeutic potential of fatty acid synthase (FASN) inhibition with FT‐4101, a potent, selective, orally bioavailable, small‐molecule by (a) evaluating the dose−response of single FT‐4101 doses (3, 6 and 9 mg) on hepatic de novo lipogenesis (DNL) in healthy participants (Study 1) and (b) demonstrating the safety, tolerability and efficacy on hepatic steatosis after 12 weeks of FT‐4101 dosing in patients with non‐alcoholic fatty liver disease (NAFLD; Study 2). Materials and Methods: In Study 1, three sequential cohorts of healthy men (n = 10/cohort) were randomized to receive a single dose of FT‐4101 (n = 5/cohort) or placebo (n = 5/cohort) followed by crossover dosing after 7 days. Hepatic DNL was assessed during fructose stimulation from 13 C‐acetate incorporation. In Study 2, men and women with NAFLD (n = 14) randomly received 12 weeks of intermittent once‐daily dosing (four cycles of 2 weeks on‐treatment, followed by 1 week off‐treatment) of 3 mg FT‐4101 (n = 9) or placebo (n = 5). Steady‐state DNL based on deuterated water labelling, hepatic steatosis using magnetic resonance imaging‐proton density fat fraction and sebum lipids and circulating biomarkers were assessed. Results: Single and repeat dosing of FT‐4101 were safe and well tolerated. Single FT‐4101 doses inhibited hepatic DNL dose‐dependently. Twelve weeks of 3 mg FT‐4101 treatment improved hepatic steatosis and inhibited hepatic DNL. Decreases in sebum sapienate content with FT‐4101 at week 11 were not significant compared to placebo and rebounded at week 12. Biomarkers of liver function, glucose and lipid metabolism were unchanged. Conclusions: Inhibition of FASN with 3 mg FT‐4101 safely reduces hepatic DNL and steatosis in NAFLD patients.